NOVEL JOKOWI SI TUKANG KAYU KARYA GATOTKOCO SUROSO SEBAGAI MATERI AJAR APRESIASI SASTRA DI SMA: KAJIAN PSIKOLOGI SASTRA DAN NILAI KARAKTER - Inung Handarini; Kundharu Saddhono; Atikah Anindyarini (Universitas Sebelas Maret, 2018)
The purpose of this research is to describe and explain: (1) the characterization of the figures in the novel Jokowi Si Tukang Kayu by Gatotkoco Suroso, (2) the inner conflict experienced by the main figure, (3) the values of character education in the novel Jokowi Si Tukang Kayu by Gatotkoco Suroso, (4) the relevance of the values of character education as teaching materials of literature appreciation in senior high school. This research is a descriptive qualitative research which used pscychology literature. The technique of data analysis used was interactive analysis technique. The result of this research showed that the characterization of the figures in the novel Jokowi Si Tukang Kayu by Gatotkoco Suroso are described through three dimensions, dimension of psysiological, psychological, and sociological. Novel Jokowi Si Tukang Kayu also contained 18 values of character education, that are religious, honest, tolerance, discipline, hardwork, creative, independent, democratic, curiosity, spirit of nationality, love the motherland, appreciating achievement, friendly/ communicative, love and peace, loving to read, care for the environtment, social care, and responsibility. Novel Jokowi Si Tukang Kayu is relevant to be used as teaching materials of literature appreciation in senior high school at class XII.